Land use influences on adjacent ecological systems: implications for conservation planning - Wade, Alisa Ann, author; Laituri, Melinda J., advisor; Theobald, David M., advisor; Hoeting, Jennifer A., advisor (Colorado State University. Libraries, 2009)
This research investigated the spatial relationships between land uses, primarily urbanization, and adjacent ecological systems. As anthropogenic stressors encroach on protected areas and aquatic systems, the ecological functioning of those systems is reduced, and this has implications for natural resource management and conservation. I conducted three separate studies to address different research questions relating to land use and land cover-ecological system linkages. I assessed the vulnerability of conservation lands throughout the U.S. to adjacent anthropogenic threats and identified protected lands that are likely threatened by human activities as well as unprotected lands that offer opportunities for future conservation action. I also quantified the amount of residential development encroachment surrounding protected lands in the U.S., and I quantified how encroachment has altered the landscape structure around conservation lands nationally from 1970 through 2000, and forecast changes for years 2000 through 2030. Results from these two studies showed that there are a number of protected areas that are vulnerable to neighboring threats and that development has both reduced the buffer surrounding and the connectedness between protected areas. However, results also suggested that there are a number of options for future conservation action, although continued urbanization will limit these options. These studies indicate that conservation planning must consider adjacent land uses. However, the final study presented in this dissertation illustrated that conservation scientists and land managers must recognize the limitations of their approach when modeling the relationships between ecological systems and adjacent land use. I used a conceptual model of how land cover at different upslope scales influences aquatic integrity to show how different modeling approaches can substantially alter resulting inference. Results suggest that a modeling approach that incorporates ecological knowledge may provide more relevant inference for management decisions. A finding applicable to all three studies is that a key conservation strategy will be to work cooperatively with adjacent land owners and mangers to successfully manage both protected areas and aquatic systems.
Keywords: conservation planning; protected areas; urban development; conservation; natural resource management; land use planning; conservation biology